Prevalence of Various Respiratory Viruses in the Middle Ear during Acute Otitis Media - Heikkinen, Terho; Thint, Monica; Chonmaitree, Tasnee (The New England journal of medicine, 1999)
Acute otitis media is the most common bacterial infection among children and the most frequent reason for outpatient antibiotic therapy. 1 Despite proper antibiotic treatment, middle-ear effusion may persist for weeks or months, 2 , 3 often resulting in repeated courses of antibiotics and, eventually, surgical intervention. 4 In the United States, the annual costs of otitis media have been estimated to exceed $3.5 billion. 5 Although acute otitis media is generally considered a bacterial infection, there is ample evidence that respiratory viruses have a crucial role in the etiology and pathogenesis of this disease. 6 , 7 Moreover, viruses may also profoundly affect the outcome of . . .